Performance of Mutual Funds In INDIA: 2000 - 2006. - Kabra, Krishna (2006)
Numerous scholarly researches have been carried out to evaluate the performance of mutual funds. These researches may differ in time period but most studies conclude that mutual funds on average have failed to outperform the market and therefore the efficient market hypothesis holds good. This research is carried out to evaluate the performance of 20 surviving diversified equity growth mutual funds for the period of 6 years from July 2000 to June 2006. The data of the fund is collected on Monthly basis. Funds are evaluated using the risk-adjusted measures like the Sharpe and Treynor ratio. 75% of the funds selected for measurement deliver positive returns and outperform the market portfolio the benchmark index BSE 500.